The blood the waterway on which life depends ([S.l.] : Transtel Cologne [production company] ; England : Audia Visual Source Video Training [distributor])
Documentary on blood circulation in human body and analysis of blood
Copy available in DVD format
Keywords: Blood; Blood -- Analysis; Blood -- Circulation